Effects of pentagamavunon-0 on histaminemediated hyperresponsive airway in asthmatic models : in-vitro in-vivo - Agung Endro Nugroho; Hemmy Prasetyo; Djoko Suhardjono; Mulyono Zhang Be; Shuang Liu; Supardjan A. Margono; Kazutaka Maeyama (Indonesian Journal of Pharmacy, 2010)
Asthma  is  a  chronic  inflammatory  airway  disease  involving  reversible airway  constriction  and  airway  hyperresponsiveness  (AHR)  to  allergens,  airway edema,  and  increased  mucus  secretion  tumor  cells.  To  date,  exploration  of antiasthmatic  drug  is  still  being  studied  both  from natural  products  or  sinthetic processes.  One of the sinthetic compound is pentagamavunon-0  (PGV-0)  which possesses anti-inflammatory and inhibitory effects on histamine release from rat mast cells. The aim of the study is to look at the effects of PGV-0 on histaminemediated hyperresponsive airway in asthmatic models (in vitro and in vivo studies).  In  vitro  study  was  conducted  using  isolated  organ  technique  with isotonic  transducer.  The  results  have  shown  that  PGV-0  could  not  inhibit  the contraction  of  isolated  guinea  pig  trachea  induced  by  histamine.  PGV-0 did not change  the  pD2 and  Emax  values  of  histamine  on  trachea  smooth  muscle.  The finding  indicates  that  PGV-0  does  not  have  affinity and  intrinsic  activity  on  H-1 histaminergic  receptor  in  trachea  smooth  muscle.  In vivo  study,  we  sensitized the  rats  with  ovalbumin  (OVA)  to  develop  the  airway hyperreactivity  to histamine.  Histamine  level  in  bronchoalveolar  lavage  fluid  (BALF)  and  airway tissue  were  determined  using  HPLC-fluorometry.  Multiple  exposures  of ovalbumin  significantly  histamine  level  in  BALF  by  74.51±5.33  pmol/mL  or 6-times  higher  than  this  of  control  saline  group.  Oral  administration  of  PGV-0 (40  mg/kg  BW)  significantly  decreased  the  histamine accumulation  in  BALF  to 30  %  of  the  value  of  control  group  in  asthmatic  rats.  Besides,  PGV-0 significantly  prevented  the  histamine  decrease  in  asthmatic  rats  to  37.8  % trachea, and 34.2 % in bronchus. However, PGV-0 did not succeed to prevent the histamine decrease in the lung of asthmatic rats.  The result of the study may provide useful information for further discovering pharmacological synthetic compound for treatment of allergic inflammatory asthma.Key words: asthma, curcumin, pentamavunon-0, histamine, airway hyperresponsiveness